Analisis Kriminologis terhadap Anak sebagai Pelaku Tindak Pidana Pencurian (Studi Kasus Putusan Pengadilan Negeri Tabanan Nomor 14/Pid.Sus/2014/PN.Tbn) - Paramahan, Marchello Gabriel; Taun, Taun (Verdict: Journal of Law Science, 2025)
This study aims to analyze the legal considerations of the judges in the Tabanan District Court Decision No. 14/Pid.Sus/2014/PN.Tbn regarding children as perpetrators of theft, as well as to examine the criminological factors that underlie the child’s criminal behavior and its relevance to the imposed criminal sanctions. The research applies a normative legal method using statutory, case, and conceptual approaches. The findings indicate that the panel of judges accurately applied the elements of aggravated theft and complied with juvenile justice procedures, including the use of social investigation reports, legal assistance, and parental involvement. However, substantively, the decision has not fully reflected the principles of restorative justice and the best interests of the child as mandated by the Juvenile Criminal Justice System Law (UU SPPA). From a criminological perspective, the child’s action was influenced by inadequate parental supervision, negative peer influence, economic pressures, psychological immaturity, and situational opportunities to commit the crime. These factors demonstrate that the child’s behavior is situational and should be addressed through rehabilitative rather than punitive imprisonment measures. Therefore, this study emphasizes the need to optimize the implementation of restorative justice in juvenile cases to ensure the achievement of protection and rehabilitation objectives.